Complicações na reabilitação bucal com implantes osseointegravéis - Ramalho-Ferreira, Gabriel [UNESP]; Faverani, Leonardo Perez [UNESP]; Gomes, Paulo Cesar Machado; Assunção, Wirley Gonçalves [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2010)
The oral rehabilitation now has a powerful ally: the dental implants. There is no denying the importance of the implant within the context of dental practice. Initially indicated for the rehabilitation of fully edentulous patients, now has gained growing space, with indications for partial edentulism, multiple unit, with high predictability of success in esthetic restorations, combined with the techniques of manipulation of soft tissues, and guided tissue regenerationearly prosthetic loading. But like any dental procedure, whether surgical or medical implantology is also subject to the occurrence of failures and complications. This paper aims to provide a review of the literature for discussion of these complications, their causes, their managements and proservation.

A reabilitação bucal conta hoje com um forte aliado: os implantes osseointegráveis. Não há como negar a importância da implantodontia dentro do contexto da prática odontológica. Inicialmente indicada para a reabilitação de pacientes totalmente edêntulos, atualmente vem conquistando espaço cada vez maior, com indicações para edentulismos parciais, múltiplos e unitários, com grande previsibilidade de sucesso nas restaurações estéticas, aliada às técnicas de manipulação de tecidos moles, regeneração tecidual guiada e carregamento protético precoce. Porém como em todo procedimento odontológico, quer seja cirúrgico ou clínico, a implantodontia também está sujeita à ocorrência de falhas e complicações. O presente trabalho tem por objetivo promover uma revisão da literatura para discussão dessas intercorrências, suas causas, seus manejos e proservação.
Complications in oral rehabilitation with dental implants
Keywords: Dental implants; Rehabilitation; Postoperative complications; Implantes dentários; Reabilitação; Complicações pós-operatórias